Primary surveillance radar (PSR) and secondary surveillance radar (SSR) of martello S743D detection optimization through automatic dependent surveillance-broadcast (ADS-B) adaptation / Abdullah 'Irfan Abdullah - Abdullah, Abdullah 'Irfan
This paper presents the analysis of Primary Surveillance Radar (PSR) and Secondary Surveillance Radar (SSR) of Martello S743D radar detection by adapting the aircraft information from Automatic Dependent Surveillance — Broadcast (ADS-B) receiver. It is performed by taking the detection information from both sensor and the comparison of the information by using the MATLAB Graphical User Interface (GUI). This research will show the functional of ADS-B receiver will solve the cone of silence of the PSR and SSR detection.